Natural Pigments from the Gall Oak (Quercus infectoria Olivier) Shellac - Yildiz, Y.; Gunes, A.; Yalcin, B.; Karadag, R. (Asian Journal of Chemistry, 2013)
In this study, the extract that contains the tannins of gall oak plants (Quercus infectoria Olivier) shellac (gallic acid, ellagic acid, tannic acid) and its derivatives were obtained separately. The natural organic pigments were obtained by supplementing aluminum(III) and iron(II) metals into these extracts. 10, 20, 30, 40 and 50 mL solutions of each metal were created by adding to the extract obtained from plants. Qualitative analyses were done with reserved-phase high performance liquid chromatography (RP-HPLC-DAD) of pigments. Gallic acid and ellagic acid constituting pigment with metals in aluminum tannin and iron tannin were determined by comparing their standards. Reversed-phase HPLC with diode-array UV-visible spectroscopic detection has been used in this identification. The extraction of dyestuffs from the natural pigments were carried out HCl/methanol/water (2:1:1; v/v/v) solution. From the results of the HPLC analysis of the gall-oak shellac pigments, it was determined that gallic acid and ellagic acid present in the natural pigments were precipitated by Al(III) and Fe(II).